2018
DOI: 10.5194/acp-18-8893-2018
|View full text |Cite
|
Sign up to set email alerts
|

Local time dependence of polar mesospheric clouds: a model study

Abstract: Abstract. The Mesospheric Ice Microphysics And tranSport model (MIMAS) is used to study local time (LT) variations of polar mesospheric clouds (PMCs) in the Northern Hemisphere during the period from 1979 to 2013. We investigate the tidal behavior of brightness, altitude, and occurrence frequency and find a good agreement between model and lidar observations. At the peak of the PMC layer the mean ice radius varies from 35 to 45 nm and the mean number density varies from 80 to 150 cm−3 throughout the day. We al… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…These calculations represent the lowest critical saturations currently assumed in mesospheric models (e.g. Berger and Lübken, 2015;Schmidt et al, 2018). However, it is expected that the majority of MSPs in the mesopause is smaller than r = 1.2 nm (Bardeen et al, 2008;Megner et al, 2008a, b;Plane et al, 2014).…”
Section: Critical Saturation For Ice Activationmentioning
confidence: 97%
See 1 more Smart Citation
“…These calculations represent the lowest critical saturations currently assumed in mesospheric models (e.g. Berger and Lübken, 2015;Schmidt et al, 2018). However, it is expected that the majority of MSPs in the mesopause is smaller than r = 1.2 nm (Bardeen et al, 2008;Megner et al, 2008a, b;Plane et al, 2014).…”
Section: Critical Saturation For Ice Activationmentioning
confidence: 97%
“…Additional studies have shown that during NLC season local temperatures are highly variable with mean temperatures of about 140 K and extremes as low as 100 K (Lübken et al, 2009;Rapp et al, 2002). Typical H 2 O concentrations of a few parts per million (Hervig et al, 2009;Seele and Hartogh, 1999) then lead to highly supersaturated conditions, i.e. saturation ratios exceeding S h = 100 are frequently observed (Lübken et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Satellites mostly operate in sun-synchronous orbits and are thus not able to cover NLC local time variations, with some exceptions (e.g., Stevens et al, 2009;De-Land et al, 2011). NLC variability during the solar day was also investigated by models (e.g., Stevens et al, 2010Stevens et al, , 2017Schmidt et al, 2018). In general, maximum values for occurrence and brightness are found in the first half of the solar day, which is attributed to temperature tides and tidal variations in background water vapor.…”
Section: Simultaneous Solar and Lunar Tidal Variationsmentioning
confidence: 99%
“…activation temperatures currently assumed in mesospheric models (e.g. Berger and Lübken, 2015;Schmidt et al, 2018). For < 1.1 nm, the size of most MSPs in the polar summer mesopause (Bardeen et al, 2010;Megner et al, 2008a;Megner et al, 2008b;Plane et al, 2014), the new activation model excluding solar irradiation predicts ice particle formation at higher temperatures than currently assumed in models.…”
Section: The Impact Of Solar Radiation On Ice Particle Formation 10mentioning
confidence: 93%
“…Either activation-barrier free growth is assumed to set in for saturations in excess of the equilibrium saturation over the curved particle surface (e.g. Berger and Lübken, 2015;Schmidt et al, 2018), or ice particle formation is described using classical nucleation theory (e.g. Asmus et al, 2014;Bardeen et al, 2010;Rapp and Thomas, 2006;Wilms et al, 2016).…”
Section: Introductionmentioning
confidence: 99%